PENGARUH PERCEIVED ORGANIZATIONAL SUPPORT, MOTIVASI INTRINSIK, DAN PERSON JOB-FIT TERHADAP JOB SATISFACTION - Roji, Fahrul; Kurniawan, Ignatius Soni (STKIP Persada Khatulistiwa Sintang, 2024)
A company's performance is mostly influenced by its human resources' capacity to adapt, develop, and contribute fully to the business. The primary element to gaining a competitive advantage is to implement effective and innovative HR management techniques. Companies must assure employee work satisfaction because it has a direct impact on productivity, retention, and the organizational image. This study aims to analyse the effect of perceived organisational support, intrinsic motivation, and person-job fit on job satisfaction among employees of PT Mitra Tirta Buwana Tbk Yogyakarta. This research is quantitative and uses primary data obtained from filling out questionnaires taken with the census technique on respondents. Data collection using direct surveys was processed using multiple linear regression analysis, preceded by classical assumption tests utilising the SPSS software application. The results stated that perceived organisation support has a significant positive effect on job satisfaction, intrinsic motivation has a significant positive effect on job satisfaction, and person-job fit has a significant positive effect on job satisfaction. The implication is that companies can increase antecedents to strengthen their employees' job satisfaction